Remote multicomponent rehabilitation compared to standard care for survivors of critical illness after hospital discharge (iRehab): a protocol for a randomised controlled assessor-blind clinical and cost-effectiveness trial [version 1; peer review: 2 approved] - Julie Bruce; Jason Madan; Martin Underwood; Roger Kenyon; Miriam Ratna; Ranjit Lall; Gavin D Perkins; Ella Terblanche; Kerry Raynes; Brenda O'Neill; Mandana Zanganeh; Rowena Williams; et al. (NIHR Open Research)
Background The consequences of critical illness can be substantial and multifactorial, encompassing physical deconditioning, mental health impairments, fatigue, and declines in health-related quality of life. We hypothesise that for people discharged after intensive care unit (ICU) for a critical illness, a six-week remote multicomponent rehabilitation intervention improves health-related quality of life, physical function, fatigue, mood, and other health-related outcomes after eight weeks, compared to standard care. Methods This is a pragmatic, randomised controlled, open-label, assessor blind, multicentre, clinical and cost effectiveness trial with internal pilot and embedded process evaluation. Recruitment will take place in NHS hospitals across the UK. Adults (n=428: control n= 197; intervention: n=231) within 12 weeks of discharge from hospital following an ICU admission for critical illness, requiring mechanical ventilation ≥48hours will be recruited. The intervention is a six week multicomponent, structured, rehabilitation programme, delivered remotely by a trained intervention team. The intervention includes four components: weekly symptom management; targeted exercise; psychological support, and peer support and information. The control group will receive standard NHS care. The primary outcome is Health-related quality of life (HRQoL) at eight weeks post-randomisation measured using the EQ-5D-5L. Secondary outcomes are: HRQoL (six months), physical function, fatigue, anxiety and depression, healthcare resource use at eight weeks and six months and intervention acceptability. Conclusions This trial will test a centrally delivered mulitcomponent rehabilitation intervention for survivors of critical illness, irrespective of geographic location or critical illness diagnosis. Trial registration The trial is registered (04.07.2022) with the International Standard Randomised Controlled Trial Number (ISRCTN) Register ISRCTN11266403 https://doi.org/10.1186/ISRCTN11266403